Optimizing Parameters of Xylenol Neodymium Imprinted Polymers (Nd-IPs) for Neodymium (III) Ions Adsorption - Azis, Muhammad Yudhistira; Wahyuni, Sri; Phiannissha, Cessoria; Zulfikar, Muhammad Ali; Setiyanto, Henry (Journal of Research and Development on Nanotechnology, 2022)
Performance evaluation of metal Neodymium Imprinted Polymers (Nd-IPs) through the polymerization of methyl metaacrylate with divinyl benzene in the presence of a metal complex Nd(III)-Xylenol Orange (XO) has been investigated. The adsorption capability towards Nd(III) ion were optimized based on ion retention parameters, such as pH, contact time, concentration, adsorption isotherm, and kinetic studies. The synthesized Nd-IPs obtained Nd(III) adsorption capacity reached 30.36 mg.g-1 at a pH of 5 with 20 minutes contact time. The isotherm studies showed the preference of Freundlich isotherm over Langmuir isotherm. The selectivity coefficient of Nd-IPs to ion Nd+3/La+3 are 1.35 and 1.38, then selectivity coefficient value obtained 1.35 and 1.40 for Nd+3/Y+3.